TERAPI MUROTTAL AL-QUR’AN DAN TERAPI DZIKIR TERHADAP PENURUNAN NYERI PASIENPOST LAPARATOMI - Fadli Syamsuddin; Rahmat Kadir (-, 2021)
Pain is a clinical manifestation that is experienced by the patient of post operation and one of the pain management is nonfarmacology therapeutic in the form of distraction. The aim of the research is to find out the therapeutic of Murottal Al-Qur’an and Dhikr toward the reduction of pain scale of the patient of post Laparatomy. The design of the research is Quasy Experiment of Non Equivalent Control Group Pretest Postest. The sample consist of 14 people with accidental sampling technique and the data is analiyzed by using Paired Sample Test. The result showed that the intensity of the pain is reduced from moderate pain to mild pain with mean difference 1.875 with the statistical test is p=0,000 (p<0,05) therefore it can be concluded that Murottal Al-Qur’an and Dhikr therapy gives impact on the reduction of pain scale.